An Evaluation of Academic- and Cultural-Based Service-Learning as Critical Pedagogies for Student Learning : Academic- and Cultural-Based Service-Learning - Simons, Lori (Advances in Social Sciences Research Journal, 2021)
A cross-sectional study was conducted to evaluate differences in students learning outcomes for 328 undergraduate students enrolled in psychology courses that utilize academic- and cultural-based service-learning as primary pedagogical methods. Results from a repeated measures analyses of covariance indicate that students improve their awareness of White privilege and understanding of gender and racial discrimination from the beginning to the end of the course. Cultural-based service-learners also had a deeper understanding of White privilege, gender and racial discrimination, and racial and economic disparities in the community, as well as stronger perspective-taking skills, ethnocultural empathy, and interpersonal engagement compared to academic-based service-learners. Results from a repeated measures analysis of variance further indicate that upperclassmen develop a racial-cultural-ethnic identity; while, underclassmen develop ethnocultural awareness over time. Implications for incorporating critical service-learning pedagogies in beginning, middle, and ending psychology courses are discussed.